Polyethylene Components in Primary Total Knee Arthroplasty: A Comprehensive Overview of Fixed Bearing Design Options - Kahlenberg, Cynthia A.; Chalmers, Brian; Sun, Hyung Jin; Mayman, David J.; Westrich, Geoffrey H.; Haas, Steven B.; Sculco, Peter K. (The Journal of Knee Surgery, 2021)
The articular design of a polyethylene insert influences the kinematics and overall function of a total knee arthroplasty (TKA). Standard symmetric posterior-stabilized and cruciate-retaining polyethylene designs have a long track record of high patient satisfaction and longevity in TKA. However, the number and variety of polyethylene inserts and articulations have continued to evolve in an attempt to better replicate native knee kinematics or provide additional constraint. Ultracongruent polyethylene designs have been touted as increasing stability while maintaining the benefits of cruciate-retaining knees. Medial pivot and lateral/dual pivot polyethylene designs were introduced to mimic more normal knee kinematics with regard to femoral rollback. Further, with increasing recognition of knee instability as a cause for persistent symptoms and revision TKA, the utilization of midlevel constraint polyethylene inserts has been increasing, with multiple implant companies offering an insert design with increased constraint for use with a primary femoral component. In this rapidly evolving arena in with a myriad of options available, surgeons should be knowledgeable about the design concepts and their applicable uses for specific patient scenarios. Future research is needed to better understand whether a particular type or design of polyethylene insert and articulation leads to improved patient reported outcomes, improved replication of knee kinematics, and long-term durable implant survivorship.
Keywords: knee arthroplasty; polyethylene design; primary total knee; knee design; polyethylene component